ANALISIS FILOSOFIS TUJUAN PENDIDIKAN AGAMA ISLAM: PERSPEKTIF ULAMA KLASIK DAN KONTEMPORER (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines philosophically the objectives of Islamic Religious Education from the perspectives of classical and contemporary Muslim scholars. Using a qualitative approach, this research applies library research and document analysis. The data were gathered from the works of Islamic education scholars and recent academic articles. The analysis was conducted through qualitative content analysis using ontological, epistemological, and axiological perspectives. The findings reveal that classical scholars emphasized moral formation, purification of the soul, closeness to Allah, and the integration of knowledge and practice as the main objectives of Islamic Religious Education. Contemporary scholars preserve these foundations while extending them toward the development of civilized, critical, adaptive, and socially responsible individuals who can respond to modern challenges. Philosophically, both perspectives are connected through the principles of tawhid and holistic human development, although they differ in contextual emphasis and practical orientation. This study highlights the importance of synthesizing the classical legacy and contemporary thought to formulate more holistic, contextual, and relevant objectives for Islamic Religious Education.